The Role of Youth in Managing Educational Startup: Case Study of PrivatQ Startup - Adkha Bukhori (Research Horizon, 2021)
Technological advances in the 4.0 era have had an impact on competitive job opportunities and declining productive jobs. In addition, starting a business requires more effort. This reality encourages young PrivatQ entrepreneurial managers to accept the test of personal advantage. The research objective is to determine the role of youth in managing educational startups and assessing their implications for the manager's personal endurance. The research using qualitative research methods. Data collection is done through interviews, focus group discussions, observations, documentation, literature, and online studies. Data analysis techniques using descriptive analysis by coding and reducing data through Nvivo 12 software, data presentation, and conclusion drawing. The results showed that youth managers played a role in managing educational startups at PrivatQ based on non-formal education services. The form of the role is in the form of governance management, program innovation, increasing access to the education service system, improving the quality and welfare of teachers, acting out of the box, and increasing soft skills and experience. The management of the educational startup has implications for the manager's personal endurance. Therefore, the role of youth managers must be increased to develop the manager's personality so that the struggle and courage so that management continues well.